IMPROVISASI STRATEGI DAN METODE DAKWAH BAGI REMAJA - Sofyan Rofi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
The phenomena of teenagers who always gather and socialize in certain places are a common thing in society. Teenagers tend to gather in one favourite place and make the place a ‘base camp’ for the group. Popular places such as cafes, wi-fi areas and others constitute a favourite place for teens to gather and socialize. A sense of comfort in that place is basically a prospect for Islamic preaching in providing religious knowledge. This condition, however, also poses a challenge for Islamic preaching requiring high level of creativity in practice. Improvisation in giving knowledge of Islam, therefore, is a necessity. Improvisation in raising religious awareness is needed so that teenagers feel comfortable in accepting Islamic values. The study adopted a qualitative approach. The participants were selected using purposive sampling comprising primary and secondary data. Primary data were data that were obtained directly from observations and interviews, while secondary data were obtained primarily from analysing some documents. The study was conducted in the sub-district area of Ambulu. The techniques for collecting data included observation, interviews, and documentation. Data analysis was conducted through reduction, data display and verification (conclusion drawing). To test the validity of the data analysis, triangulation technique was carried out. The conclusion of this study is the improvisation of preaching strategies used includes increasing teenagers' understanding by means of personal approaches, participatory approaches, and youth empowerment.